Definition the effect of vacuum-contact thermal process the wood of ash-tree on its physical and mechanical properties - Ilkiv, Myhaylo; Huber , Yuriy (Forestry, Forest, Paper and Woodworking Industry, 2024)
Method and results of the experimental investigation of physicals and mechanicals properties change the wood of ash-tree of the vacuum-contact thermal process. Mathematical and graphic dependences are got physicals and mechanicals properties the wood of ash from operating conditions of the thermal process.